Selected Decisions Annex (14th Ed). (Selected Decisions; Issue, Year, 1989)
This paper discusses several IMF's selected decisions of the Executive Board and related documents annex to fourteenth issue. Pursuant to Section III, paragraph 2 of the Instrument to Establish the Enhanced Structural Adjustment Facility Trust, the IMF in its capacity as Trustee of that Trust, approves the agreement for borrowing from the Caisse Centrale de Cooperation Economique in terms of the draft set out in the attachment to EBS/88/62, and authorizes the Managing Director to take such action as is necessary to conclude and implement the agreement. The amount of the loan shall be the equivalent of SDR 800 million. Interest in respect of each drawing shall be paid six calendar months after the drawdown date and every six calendar months thereafter. If any amount of interest is not paid to the Bank within a period of 10 days after the due date, the Trustee shall not make further drawings or give initial or final notice of a drawing under this agreement pending consultations with the Bank on the matter.